Natural-Based Antioxidant Extracts as Potential Mitigators of Fruit Browning - Cindy Dias; Alexandre M. A. Fonseca; Ana L. Amaro; Ana A. Vilas-Boas; Ana Oliveira; Sonia A. O. Santos; Armando J. D. Silvestre; Sílvia M. Rocha; Nélson Isidoro; Manuela Pintado (MDPI AG, 2020)
Fruit enzymatic browning (EB) inhibition continues to be a challenge in the Food Industry. This physiological disorder results mainly from the oxidation of natural phenolic compounds by polyphenoloxidase (PPO) and peroxidase (POX) leading to the formation of brown pigments. EB can be controlled with the application of antioxidants, reducing/inhibiting the activity of these oxidative enzymes. In this study, strawberry tree (leaves and branches) and apple byproduct were the natural-based extracts (NES) selected, as potential tissue browning inhibitors, within a first screening of fifteen natural-based extracts with antioxidant properties. Phenolic profile, total phenolic content and antioxidant activity of the selected extracts were also performed as well as their depletion effect on the oxidative enzyme's activity and browning inhibiton in fresh-cut pears. Strawberry tree extracts (leaves and branches) revealed higher total phenolic content (207.97 ± 0.01 mg GAE.gNES−1 and 104.07 ± 16.38 mg GAE.gNES−1, respectively), confirmed by the plethora of phenolic compounds identified by LC-ESI-UHR-QqTOF-HRMS and quantified by HPLC. This phytochemical composition was reflected in the low IC50 against PPO and POX obtained. Despite the lower phenolic content (6.76 ± 0.11 mg GAE.gNES−1) and antioxidant activity (IC50 = 45.59 ± 1.34 mg mL−1), apple byproduct extract showed potential in delaying browning. This study highlights the opportunity of byproducts and agricultural wastes extracts as novel anti-browning agents.